Deficiency judgments as a mortgage pricing factor - Tomasz Pruszkowski (International Journal of Management and Economics, 2017)
The subject of the deficiency judgments has been poorly examined due to a lack of relevant data and the complexity of the issue. Some comprehensive studies have explored whether allowing deficiency judgments decreases the likelihood of strategic defaults in the U. S. mortgage market. Little, however, has been done to determine whether there is any direct correlation between legal standing allowing recourse and loan pricing. Hence, additional work regarding this subject is needed. This study seeks to fill this gap by exploring the impact of allowing deficiency judgments on mortgage pricing policy in various U. S. states. Seven distinctive mortgage types in two groups of states were compared. We conclude that there is no statistically significant difference between recourse and non-recourse states in terms of mortgage pricing, regardless of mortgage type.
Keywords: G21; G28; K25; K35; 650; deficiency judgment; recourse and non-recourse mortgages; mortgage pricing policies